Alienation in a four factor world. (7th December 2018) - Silver, Daniel
Abstract: This paper aims to reconstruct the concept of alienation as a live topic for active social theorizing. Joining Marxian and Simmelian ideas, it provides a multi‐dimensional, formal, and synthetic theory of alienation. The paper develops a set of theoretical tools for articulating formal elements of action that make alienation possible, without giving conceptual priority to alienation in the sphere of production, or within that sphere to the alienation of labor. These tools make it possible to derive classical notions of alienation as specific, contingent combinations of multiple elements, theorizing them as concrete socio‐historical configurations of a broader universe of possibilities. They also organize systematic reflection on various forms and relations of alienation; not only those between for instance labor and capital, but also among all four factors of production: land, labor, capital, and entrepreneurship. The paper accordingly develops an original, multi‐dimensional theorization of alienation for a complex, pluralistic world.